As Minas setecentistas e autorias femininas na história e crítica de arte - Vermeersch, Paula Ferreira [UNESP] (Instituto de Estudos Brasileiros, 2024)
In Brazilian history and art criticism, the so-called mineiro baroque was the object of study in researches considered fundamental today in the understanding of artistic phenomena in the country. From the examination of texts by Judith Martins (1903-2000), Hanna Levy (1912-1984) and Myriam Ribeiro de Oliveira (1943), the importance of these authors in the consolidation of the area of studies on the arts in Minas Gerais in the 18th century is highlighted, within a broader panorama of the work of women, responsible for studying, cataloging and preserving the heritage of the historical cities of Minas Gerais.

Na história e na crítica de arte brasileiras, o chamado barroco mineiro foi objeto de estudo de pesquisas consideradas hoje fundamentais na compreensão dos fenômenos artísticos no país. A partir do exame de textos de Judith Martins (1903-2000), Hanna Levy (1912-1984) e Myriam Ribeiro de Oliveira (1943), a importância destas autoras na consolidação da área de estudos sobre as artes em Minas Gerais do século XVIII é ressaltada, dentro de um panorama mais amplo de atuação de mulheres, responsáveis pelo estudo, catalogação e preservação do patrimônio das cidades históricas mineiras.
Eighteenth-century Minas and female authors in art history and criticism
Keywords: XVII Century; Minas Gerais; history and criticism; Século XVIII; Minas Gerais; história e crítica